Screening for musculoskeletal system malformations and birth injuries in newborns: Results of a screening program in two hospitals in Shenzen, China. Issue 3 (20th June 2022) - Xiong, Zhu; Zhao, Zhenhui; Deng, Hansheng; Qiu, Xin; Li, Weiqing; Chen, Xiaodi; Tang, Yu; Han, Shuai; Zhao, Jiaxin; Cai, Ting; Liu, Xian; Zeng, Shuaidan; et al.
ABSTRACT: Importance: There are a variety of musculoskeletal malformations and injuries that can occur in newborns. These can be a significant cause of perinatal death or a reason for miscarriage and can lead to long‐term functional issues if not managed appropriately. There is no systematic and well‐established screening program for neonatal musculoskeletal malformations and injuries in China now. Objective: To report the incidence and types of congenital musculoskeletal malformations in two hospitals in Shenzhen City, to explore and discuss the details of the screening procedure and improve future prevention and treatment. Methods: From October 2013 to May 2014, 2564 one‐day‐old newborns were screened by a pediatric orthopedic physical examination, in combination with ultrasonography when required, and the incidence and variety of diseases were recorded statistically. Results: Among 2564 screened newborns, the following musculoskeletal conditions were identified: congenital muscular torticollis (CMT) (seven cases, 0.27%), hip subluxation (four cases, 0.16%), hip dysplasia (47 cases, 1.83%), congenital talipes equinovarus (CTEV) (two cases, 0.08%), congenital talipes calcaneovalgus (15 cases, 0.58%), polydactyly (nine cases, 0.35%), syndactyly (one case, 0.04%), and spinal hemivertebra (one case, 0.04%). Additionally, there were five (0.19%) neonates with birth injuries. Interpretation: It is feasible to carry out neonatal screening and identification of musculoskeletal malformations and birth injuries in China. This is helpful as timely detection and early intervention for many of these conditions can avoid permanent functional impairment in these children. Abstract : There are a variety of musculoskeletal malformations and injuries that can occur in newborns. These can be a significant cause of perinatal death or reason for miscarriage and can lead to long‐term functional issues if not managed appropriately. It is feasible to carry out neonatal screening and identification of musculoskeletal malformations and birth injuries in China. This is helpful as timely detection and early intervention for these conditions can avoid permanent functional impairment in the children.